Ownership identity and role of nonprofit and for-profit hospitals - Byung Hee Min; Keon-Hyung Lee; Suk Joon Hwang; Jongsun Park (Global Business & Finance Review (GBFR), 2022)
Purpose: This study examined whether nonprofit hospitals reflect social roles as well as values and satisfy their financial responsibilities compared with for-profit hospitals. Design/methodology/approach: Using panel data from the Hospital Financial and Utilization Information Data System in Florida from 2011 to 2017, this study employed a cross-sectional time-series analysis to examine the effect of hospital ownership on uncompensated care, charity care, technical efficiency, and profit margin. Findings: Compared to for-profit hospitals, nonprofit hospitals better fulfill a social role and provide more public value by providing more uncompensated care and charity care. For-profit hospitals, however, are financially more efficient than nonprofit hospitals in terms of maximizing profit margins. When comparing hospital technical efficiency, there is no statistically significant difference between nonprofit and for-profit hospitals. As expected, nonprofit hospitals better fulfill social roles but for-profit hospitals better perform financially. Research limitations/implications: This study revealed differences in fulfilling social roles and satisfying financial responsibilities between nonprofit and for-profit hospitals. To have a longer sustainability, as the provision of health care services includes both social and financial aspects, hospitals should emphasize not just either social or financial aspect only but both aspects at the same time. Future studies should extend this research to examine the conditions of normative-oriented commitments and motivations to see how they affect various hospital identity and role in different contexts. Also, as this study employed only one state in the U.S., it is important to carefully generalize findings in this study. Originality/value: This study proposes a theory surrounding the role and function of nonprofit organizations based on a dual bottom approach, reflecting the dimensions of nonprofits' characteristics and identity.
Keywords: 650; Ownership distinction; Dual bottom approach; Nonprofit hospitals; For-profit hospitals; Social roles; Financial responsibilities